2020
DOI: 10.3390/insects11110819
|View full text |Cite
|
Sign up to set email alerts
|

Positive Correlation between Pesticide Consumption and Longevity in Solitary Bees: Are We Overlooking Fitness Trade-Offs?

Abstract: The ubiquitous use of pesticides is one major driver for the current loss of biodiversity, and the common practice of simultaneously applying multiple agrochemicals may further contribute. Insect toxicology currently has a strong focus on survival to determine the potential hazards of a chemical routinely used in risk evaluations. However, studies revealing no effect on survival or even indicating enhanced survival are likely to be misleading, if potential trade-offs between survival and other physiological fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 75 publications
(125 reference statements)
1
5
0
Order By: Relevance
“…Here, we used standard laboratory methods (Strobl et al, 2019;Strobl et al, 2020) to investigate infertility in male bees, Osmia cornuta, exposed to field-realistic concentrations of the neonicotinoid insecticide thiamethoxam. For that purpose, we measured the effects of thiamethoxam on survival, food consumption, and sperm traits.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used standard laboratory methods (Strobl et al, 2019;Strobl et al, 2020) to investigate infertility in male bees, Osmia cornuta, exposed to field-realistic concentrations of the neonicotinoid insecticide thiamethoxam. For that purpose, we measured the effects of thiamethoxam on survival, food consumption, and sperm traits.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations focusing on aspects of nesting activity including the number of nesting bees [ 60 , 78 ], number of brood cells produced [ 51 , 52 , 57 , 60 , 62 , 69 , 74 , 78 80 ], number of nests/female [ 45 , 57 , 70 ], and the number of days spent nesting have been published. The effects of exposure to pesticide mixtures on foraging activity [ 55 , 68 70 , 81 ], flight [ 71 , 73 , 81 ], food consumption by adults [ 75 , 76 , 82 ] and nesting [ 55 , 68 71 , 73 , 81 , 83 , 84 ] have also been investigated. Generally, effects observed depend on the pesticide(s) studied, and, since there are limited investigations, clear trends are difficult to establish.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in our study, the first species to emerge was O. bicornis, and the last was M. versicolor, which began emerging 5 d after the last O. bicornis had emerged. However, Strobl et al (2020) found that median longevity of female O. bicornis maintained under laboratory conditions was 21 d, and that some individuals lived for 70 d, suggesting these species could easily overlap in terms of adult activity periods.…”
Section: Discussionmentioning
confidence: 98%